2023
DOI: 10.1002/adfm.202301677
|View full text |Cite
|
Sign up to set email alerts
|

Cation Substitution Induced d‐Band Center Modulation on Cobalt‐Based Spinel Oxides for Catalytic Ozonation

Abstract: Co3O4 spinel is a promising transition metal oxide (TMO) catalyst for the catalytic ozonation of volatile organic compounds (VOCs). Herein, metal–organic frameworks (MOFs)‐derived Ni‐ and Mg‐ substituted Co3O4 catalysts retain similar spinel structures, but display improved and reduced ozonation performance of methyl mercaptan (CH3SH), respectively. Remarkably, the NiCo2O4 catalyst can still ≈90% removal of CH3SH after running for 20 h at room temperature under an initial concentration of 50 ppm CH3SH and 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…It is widely accepted that the d-band center (ε d ) can be used as a descriptor of the transition metal binding adsorbate tendency. The ε d level of the adsorption Co sites for Co 3 O 4 , Al–Co 3 O 4 , Ga–Co 3 O 4 , Fe–Co 3 O 4 , Ni–Co 3 O 4 , and In–Co 3 O 4 is −2.446, −2.820, −2.795, −2.543, −2.786, and −2.391 eV, respectively (Figure a–c and Table S12). The PDS energy barriers should present a reverse volcanic trend versus the d-band center of the adsorption Co sites (Figure i).…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that the d-band center (ε d ) can be used as a descriptor of the transition metal binding adsorbate tendency. The ε d level of the adsorption Co sites for Co 3 O 4 , Al–Co 3 O 4 , Ga–Co 3 O 4 , Fe–Co 3 O 4 , Ni–Co 3 O 4 , and In–Co 3 O 4 is −2.446, −2.820, −2.795, −2.543, −2.786, and −2.391 eV, respectively (Figure a–c and Table S12). The PDS energy barriers should present a reverse volcanic trend versus the d-band center of the adsorption Co sites (Figure i).…”
Section: Resultsmentioning
confidence: 99%
“…Qu et al. optimized the electronic structure of Co 3 O 4 spinel by different cation substitutions, thus selecting spinel materials with high catalytic activity [119] . As seen in Figure 6a, the density of states (DOS) of the spinel materials is clearly observed, three samples possess a high DOS at E f , which show strong metallicity, suggesting a fast electron transfer in MCo 2 O 4 (M=Co, Ni, Mg).…”
Section: Spinel Catalytic Activity Descriptorsmentioning
confidence: 99%
“…(h) Electron density difference diagram of reactants adsorption at the Co site on various catalyst surfaces. (a–c) Reproduced with permission [119] . Copyright 2023, Wiley‐VCH.…”
Section: Spinel Catalytic Activity Descriptorsmentioning
confidence: 99%
“…28 It has been reported that a versatile electronic structure can be achieved by controlling the vacancy concentration and selecting the substitution of either A-site or B-site ions. 29,30 However, there is limited research on the effect of selective replacement of metal ions at the octahedral site in NiCo 2 O 4 on its gas sensing capabilities.…”
Section: Introductionmentioning
confidence: 99%